Analysis of Sexual Risk Among Homosexual in Samarinda - Febriyanto, Kresna; Fadzlul Rahman, Ferry (International Journal of Psychosocial Rehabilitation, 2020)
Risky sexual behavior is any form of behavior that is based on the encouragement of sexual desires both with the opposite sex and the same sex to get pleasure in the sexual organs. Unusual deviant behavior in society is homosexual or heterosexual, that is, men who are attracted not only to women but also to men. To find out the relationship between age and risky sexual behavior in MSM (male sex), to know the relationship of emotional intelligence to risky sexual behavior in MSM (male sex), to know the relationship between knowledge level and risky sexual behavior in MSM (male sex), to find out the relationship between the environment and risky sexual behavior in MSM (male sex), and to know the relationship between media exposure (visual, audiovisual) and risky sexual behavior in MSM (male sex). This type of research is quantitative research with a cross-sectional approach. The sampling technique was the Slovin formula so that 91 respondents were obtained. The research instrument used was a questionnaire. Data analysis used in this study was Spearman (rho) on the age variable and chi square on the emotional intelligence variable, knowledge, environment, and media exposure. There is no relationship between age and risky sexual behavior in men who have sex with men in samarinda with a value of p = 0.136 (r = 0.157). There is a relationship between emotional intelligence and risky sexual behavior in homosexuals in Samarinda with a value of p = 0.031 (OR: 5.758). There is a relationship between the level of knowledge and risky sexual behavior in homosexuals with a value of p = 0.045. There is a relationship between the environment and risky sexual behavior in homosexuals in Samarinda with a value of p = 0.049. There is a relationship between media exposure and risky sexual behavior in homosexuals in Samarinda with a value of p = 0.040.